Herbal Medicine in the Treatment of Polycystic Ovary Syndrome - L Kashani; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2016)
Polycystic Ovary Syndrome (PCOS) is a hormonal disorder that affects between 5 - 10% of women who are of reproductive age. The most common symptoms of PCOS are obesity/difficulty losing weight, acne, amenorrhea (absence of menstrual cycles), irregular menstrual cycles, hirsutism (increased growth of corporal hair), insulin resistance, and high cholesterol. One of the treatments for PCOS is the use of Metformin (which is a drug prescribed to type 2 diabetics) which can help treat the insulin resistance associated with PCOS. However many women who suffer from PCOS opt to use alternative medicine in conjunction with traditional medicine to improve their condition. There are some herbs that are very helpful in treating PCOS. In this review, we focus on the role of herbal medicine in the treatment of PCOS.